Peningkatan Sikap Tanggung Jawab Lingkungan dan Keterampilan Berwirausaha melalui Proyek Pengenalan Adiwiyata di SDITNurul Hikmah - Muhamad Ikhwanus Shofa; Wahyuni Nur Ammala; Aisya Aulia (Pendidikan Dasar - Pascasarjana Universitas Negeri Jakarta, 2025)
This study aims to enhance students’ environmental responsibility and entrepreneurial skills through the introduction of the Adiwiyata project at SDIT Nurul Hikmah Sidoarjo. The research employed a Classroom Action Research (CAR) design using the Kemmis and McTaggart model, conducted in two cycles consisting of planning, action, observation, and reflection stages. The subjects of this study were 26 students from Grade 3 Hamasah. Data were collected through questionnaires, observations, interviews, and documentation, and analyzed using descriptive quantitative and qualitative methods. The results showed a significant improvement in both observed aspects. The average score of environmental responsibility increased from 61.6% in Cycle I to 81.15% in Cycle II, moving from the Developing to Highly Developed category. Meanwhile, the entrepreneurial skill aspect improved from 60.00% in Cycle I to 80.20% in Cycle II, also categorized as Highly Developed. These findings indicate that the implementation of the Adiwiyata project through the NATURA program (Natural Nutrients for Superior and Eco-Friendly Plants) effectively enhances students’ environmental awareness, responsibility, and entrepreneurial character at the elementary school level.